Analisa kesalahan Otoritas Singkatan dan Akronim pada Komentar Media Sosial - Muhammad Abi Zaard; Agung Pranoto Kaditmaja (Indo Publishing, 2026)
The use of abbreviations and acronyms is a form of language development that emerged in response to the need for fast and efficient communication in the modern era. This study aims to examine the use of abbreviations and acronyms in Indonesian, including their definitions, types, writing rules, and roles in various communication contexts. The method used is a qualitative approach with a descriptive type of research through literature study, with data collection techniques including reading, recording, and classifying relevant sources. The results of the study indicate that abbreviations and acronyms are widely used in both formal and informal contexts, with the main function of shortening the delivery of information without losing meaning. However, there are also discrepancies found in their use with language rules, especially in digital media, such as ignoring punctuation and forming non-standard forms. The discussion emphasizes that abbreviations and acronyms play an important role in efficient communication, but their use must be adapted to the context and follow applicable language rules. Thus, a good understanding is needed so that the use of abbreviations and acronyms remains effective, clear, and in accordance with good and correct Indonesian language standards.